Analysis of foreign diesel fuels and prospect of improvement of their ecological performance - Семитківська, Таїса Олексіївна (Technology audit and production reserves, 2015)
The progressive development of humanity determines the increase in energy consumption in general and diesel fuel as well. Increasing the consumption of diesel fuel leads to negative consequences. In this regard all over the world there is a problem to improve their environmental performance. A comparative evaluation of the consumption of cleaner diesel fuel and fuel with high sulfur content among the various countries of the world is conducted. On the example of the Russian Federation it is presented information on the annual emissions of combustion products. The effect of the sulfur content in diesel fuel emissions of solid particles in the exhaust gases is evaluated. The hazard of diesel soot by increasing adsorption on its surface of polycyclic aromatic hydrocarbons is proved. The effect on emissions of solid particles of fractional composition of the product and the content of aromatic hydrocarbons is considered. The hazardous effects on the environment of sulfur compounds in the diesel fuel are shown. The necessity of purposeful study the possibility of replacing the aromatic component in the fuel using a strategy of environmentally-friendly additives is proved.